1997
DOI: 10.1002/(sici)1096-8628(19970303)69:1<69::aid-ajmg13>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the 5α-steroid reductase type 2 gene in a family with deficiency of the enzyme

Abstract: This report describes the identification of a point mutation in the 5 alpha-reductase type 2 (5 alpha-SR2) gene from a family in which both sibs (6 and 3 years old) have steroid 5 alpha-reductase 2 deficiency. The five exons of the gene were individually amplified by the polymerase chain reaction (PCR) and analysed for single-strand conformation polymorphisms (SSCP) to detect mutations. Direct sequencing of the mutant PCR products demonstrated a single C-->T mutation, within exon 4, changing codon 227 from CGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Consistent with this, experimental evidence has shown that all nonsense mutations in SRD5A2 lead to the synthesis of proteins with no detectable enzyme activity (Wilson et al 1996;Vilchis et al 1997;Sasaki et al 2003;Wang et al 2004). Furthermore, the in vitro experiments of site-directed mutagenesis confirmed that the P212X mutant enzyme is devoided of catalytic activity (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Consistent with this, experimental evidence has shown that all nonsense mutations in SRD5A2 lead to the synthesis of proteins with no detectable enzyme activity (Wilson et al 1996;Vilchis et al 1997;Sasaki et al 2003;Wang et al 2004). Furthermore, the in vitro experiments of site-directed mutagenesis confirmed that the P212X mutant enzyme is devoided of catalytic activity (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Mutation of the SRD5A2 gene in codon 227 has been described in Creole Brazilians and Mexican Americans who presented with a premature termination codon (Thigpen et al, 1992; Vilchis et al, 1997). In those patients, the testes were extra‐abdominal, located in the inguinal canals, labia majora, or scrotum, but spermatogenesis was absent or was profoundly impaired in the 9 studied subjects.…”
Section: Discussionmentioning
confidence: 99%
“…AR gene exons 1–8 and SRD5A2 gene exons 1–5 were amplified by polymerase chain reaction (PCR). The primers used in the amplification of the SRD5A2 gene have been described by Vilchis et al (1997). PCR amplification of exon 1 was carried out in a volume of 12.5 μL containing 50 ng of genomic DNA, 0.5 mM of each primer, 0.375 U of FailSafe PCR Enzyme Mix, and Premix D (EPICENTRE, Madison, Wis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we selected 16 boys with severe hypospadias and cryptorchidism to sequence the SF-1 gene (2-7 exons). The primers used for the amplification of exons of the SRD5A2, AR and SF-1 genes have been described previously (7)(8)(9). PCR was performed in a final volume of 50 μL that contained 200 ng genomic DNA, 20 pmol of each primer, 200 μM dNTPs, 1.5 mM MgCl 2 and 2.5 U Taq polymerase (Sangon, Shanghai, China).…”
Section: Dna Sequence Analysismentioning
confidence: 99%